MBD2 and MBD3: elusive functions and mechanisms - Menafra, Roberta; Stunnenberg, Hendrik G. (Frontiers in Genetics, 2014)
DNA methylation is a long known epigenetic mark involved in many biological processes and the ‘readers’ of this mark belong to several distinct protein families that ‘read’ and ‘translate’ the methylation mark into a function. Methyl-CpG binding domain proteins belong to one of these families that are associated with transcriptional activation/repression, regulation of chromatin structure, pluripotency, development and differentiation. Discovered decades ago, the systematic determination of the genomic binding sites of these readers and their epigenome make-up at a genome-wide level revealed the tip of the functional iceberg. This review focuses on two members of the methyl binding proteins, namely MBD2 and MBD3 that reside in very similar complexes, yet appear to have very different biological roles. We provide a comprehensive comparison of their genome-wide binding features and emerging roles in gene regulation.